A Mixed-Methods Analysis of Negative Patient Experiences in Emergency Department Care: Identifying Challenges and Evidence-Informed Strategies Across the Care Continuum - J. K. Fujioka MPH; M. Walker PhD; D. Rajab BSc; S. A. Bartels MD (Journal of Patient Experience)
This mixed-methods study explores negative patient experiences within emergency departments (EDs), aiming to uncover systemic challenges and propose evidence-informed solutions. Of 2114 shared ED experiences, 306 (14.5%) were reported as "bad" or "very bad." Younger age, Indigenous status, financial instability, mental health disabilities, and non-heteronormative sexual identities were associated with negative ED experiences. Our research highlights key issues across the ED care continuum. During triage and registration, patients felt judged and perceived that their health concerns were under prioritized. Prolonged wait times contributed to feelings of neglect. During assessments, privacy concerns and lack of communication were prominent. Perceptions of misdiagnosis and stigmatization emerged as major concerns during the diagnosis and treatment phases. At discharge, insufficient follow-up and unclear instructions were frequently reported. Our findings underscore the need for improved communication, enhanced training to reduce stigma, and multi-pronged strategies to address the root causes of patient dissatisfaction. These insights can guide healthcare practitioners and policymakers in fostering a more inclusive and supportive ED environment, ultimately improving patient experiences and outcomes.